Draft genome sequence of Vitellibacter aquimaris D-24 T isolated from seawater - Thevarajoo, Suganthi; Selvaratnam, Chitra; Chan, Kok Gan; Goh, Kian Mau; Chong, Chun Shiong (Sociedade Brasileira de Microbiologia, 2018)
Vitellibacter aquimaris D-24T (=KCTC 42708T = DSM 101732T), a halophilic marine bacterium, was isolated from seawater collected from Desaru beach, Malaysia. Here, we present the draft genome sequence of D-24T with a genome size of approximately 3.1 Mbp and G + C content of 39.93%. The genome of D-24T contains genes involved in reducing a potent greenhouse gas (N2O) in the environment and the degradation of proteinaceous compounds. Genome availability will provide insights into potential biotechnological and environmental applications of this bacterium.